2011
DOI: 10.1002/pola.24977
|View full text |Cite
|
Sign up to set email alerts
|

Well‐defined diblock copolymers possessing fluorescent and metal chelating functionalities as novel macromolecular sensors for amines and metal ions

Abstract: The amino‐ and metal‐ion sensing capability of a novel type of well‐defined block copolymers based on 9‐anthrylmethyl methacrylate (AnMMA; hydrophobic, fluorescent) and 2‐(acetoacetoxy)ethyl methacrylate (AEMA; hydrophobic, metal chelating) has been investigated in organic media. AEMAx‐b‐AnMMAy diblock copolymers were prepared for the first time using reversible addition‐fragmentation chain transfer (RAFT) polymerization. All polymers were characterized in terms of molecular weights, polydispersity indices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Well‐defined PAMMA homopolymers were successfully synthesized following typical RAFT methodologies (Scheme ), and RAFT polymerization of AMMA was previously reported by Krasia‐Christoforou et al However, detailed kinetic studies of the polymerization were not reported, although the resulting polymer had relatively narrow PDI. Table summarizes the conditions and the results of conventional free radical polymerization and RAFT polymerization of AMMA.…”
Section: Resultsmentioning
confidence: 99%
“…Well‐defined PAMMA homopolymers were successfully synthesized following typical RAFT methodologies (Scheme ), and RAFT polymerization of AMMA was previously reported by Krasia‐Christoforou et al However, detailed kinetic studies of the polymerization were not reported, although the resulting polymer had relatively narrow PDI. Table summarizes the conditions and the results of conventional free radical polymerization and RAFT polymerization of AMMA.…”
Section: Resultsmentioning
confidence: 99%
“…The PMMA homopolymer ( M w ≈ 350 000) was purchased from Sigma‐Aldrich and used as received from the manufacturer. The poly(9‐anthrylmethyl methacrylate) ( M n = 27 900 g mol −1 , where M n is the number average molecular weight determined by size exclusion chromatography using PMMA calibration standards) was in house synthesized by RAFT controlled radical polymerization according to our previous publication . Tetrahydrofuran (THF, extra pure), that was the solvent of choice for the preparation of the polymer solutions to be electrospun, was purchased from Scharlau.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported on the synthesis of well‐defined methacrylate‐based homopolymers and block copolymers containing anthracene side‐chains functionalities. These materials were prepared by reversible addition–fragmentation chain transfer (RAFT) controlled radical polymerization and they were evaluated as dual fluorescent chemosensors for amines and transmission metal ions in solution …”
Section: Introductionmentioning
confidence: 99%
“…Along with this, anthracene's functionality is of great interest when it is used as a substrate material for crosslinking in reversible network polymeric materials because of its thermally reversible Diels–Alder [4 + 2] cycloadditions and reversible photodimerization, depending on the irradiated λ . Poly(anthracene methyl methacrylate) is a polycyclic hydrocarbon; because of its properties and interactions with other polymers and drug materials, various research teams have synthesized its polymers with conventional and controlled or living radical polymerization techniques and studied their properties for photoluminescent films, photoresists, and chemiluminescent fluorophores …”
Section: Introductionmentioning
confidence: 99%
“…To date, a limited number of reports have been published on well‐defined (co)polymer synthesis based on 9‐anthracene methyl methacrylate (AnMMA) and their photoresponsiveness . To the best of our knowledge, no report has been published on the synthesis of poly( N ‐isopropyl acrylamide‐ b ‐9‐anthracene methyl methacrylate) [poly(NIPAAm‐ b ‐AnMMA)] SRABCs with various hydrophobic poly(9‐anthracene methyl methacrylate) [poly(AnMMA)] block lengths through RAFT polymerization with poly(NIPAAm) as a macro‐RAFT agent and their self‐assembly in solution.…”
Section: Introductionmentioning
confidence: 99%